Analysis of Cybersecurity Vulnerabilities in Maritime GNSS Systems - Chinnarong, Thirawat; Pomsathit, Auttapon; Yongsiriwit, Karn (My University, 2024)
The maritime industry is increasingly dependent on Global Navigation Satellite Systems (GNSS) such as GPS, GLONASS, BeiDou, and Galileo for navigation and operational efficiency. However, these systems are vulnerable to cyber threats like spoofing and jamming, which can severely disrupt maritime operations by misleading navigation systems [1], [2]. This study analyzes the cybersecurity vulnerabilities of GNSS systems used in maritime environments, utilizing a Software-Defined Radio (SDR) to simulate GNSS spoofing attacks on various maritime GNSS receivers [3]. The findings reveal that all tested receivers are susceptible to spoofing attacks, underscoring the need for enhanced cybersecurity measures [4]. The study advocates for the development of advanced detection systems, improved signal authentication, and adherence to cybersecurity guidelines provided by organizations such as INTERTANKO and the International Maritime Organization (IMO) [5], [6]. The proposed strategies aim to mitigate the risks associated with GNSS vulnerabilities and ensure the safety and security of maritime operations.
Keywords: Cyber Threats; GNSS; GPS; HackRF; Jamming; Maritime Cybersecurity; Maritime Safety; Signal Authentication; Software-Defined Radio (SDR); Spoofing